Going beyond the injury: regulatory conditions contributing to Latina/o immigrants' occupational psychosocial stressors - Airin Denise Martinez; Abdel ePiedramartel; Jacqueline eAgnew (Frontiers Media S.A., 2015)
BACKGROUND: Utilizing a psychosocial stress approach, we report psychosocial stressors that Latina/o immigrant day laborers in Baltimore report as workplace hazards and the contextual factors that shape these stressors. METHODS: Through a community-academic partnership, we conducted focus groups (n=18) and key informant interviews (n=9) using instruments developed between academics and the community partner to inquire Latina/o immigrants' jobs, hazard awareness, occupational illnesses and injuries, and reporting behaviors. We conducted a transcript-based thematic analysis.RESULTS: The psychosocial stressors that Latina/o day laborers report as dangers at work are anxiety beating the deadline and fear from wage theft, sudden termination and immigration enforcement.DISCUSSION: More attention needs to be given to Latina/o immigrant day laborers' occupational psychosocial risks. Policies should be made to lower barriers for Latina/o immigrants to report grievances to state agencies.